Legal Consequences of Not Including The Identity of Business Actors in The Marketplace and The Role of The Marketplace Related to Fulfilling Consumer Rights - yulia shadrina (Syiah Kuala Law Journal, 2023)
Buying and selling transactions through information technology media and the internet (e-commerce) have positive and negative sides. Several problems often occur in its implementation, which often requires the seller’s accountability to not harm consumer rights. However, one element that is often forgotten by sellers and buyers is the inclusion of the identity or address of the business actor in the marketplace. As a result, fulfilling the responsibilities of the seller is often difficult and the buyer becomes disadvantaged. Not only the seller, the marketplace as a place that facilitates sellers and buyers also has an important role so that consumer rights can be fulfilled. Not including the identity/address of business actors in the marketplace also creates legal consequences that differ from several laws and regulations in Indonesia, requiring more attention from the government